Social capital in rural communities in the Netherlands - Thissen, Frans (Journal for Geography, 2009)
The quality of life in Dutch rural communities is high in comparison with urban communities in the Netherlands because of the residential quality of villages, the mobility of the inhabitants and the strong commitment by the inhabitants to the local society. However, today’s Dutch villages bear no resemblance to the traditional village and neither is social capital self-evident nowadays. This article presents evidence from two projects. It summarizes some results of a national survey organised within the framework of the research programme entitled ‘The Social State of the Countryside’, as carried out by the Social and Cultural Planning Office of The Netherlands (SCP) and a project in one of the most rural parts of the Netherlands (Zeeland). In the Zeeland villages, social capital is analysed from the point of view of the relationship between quality of life, social cohesion and local community care in small villages.
Keywords: transformation of rural communities; civil society; social capital; quality of life; social vitality; social cohesion; community care